Profiles of Rho, Opn4, c-Fos, and Birc5 mRNA expression in Wistar rat retinas exposed to white or monochromatic light - Ziółkowska, Natalia; Lewczuk, Bogdan (Frontiers in Neuroanatomy, 2022)
Despite concern over potential retinal damage linked to exposure to light-emitting-diode (LED) light (particularly blue light), it remains unknown how exposure to low-intensity monochromatic LED light affects the expression of rhodopsin (Rho, a photopigment that mediates light-induced retinal degeneration), melanopsin (Opn4, a blue-light sensitive photopigment), c-Fos (associated with retinal damage/degeneration), and Birc5 (anti-apoptotic). This study investigated the mRNA expression profiles of these genes under exposure to white and monochromatic light (blue, red, green) in the retinas of albino rats under a cycle of 12 h of light and 12 h of darkness. In each group, 32 Wistar rats were exposed to one type of monochromatic-LED or white-fluorescent light for 7 day (150 lx). Retinal samples were taken for qPCR analysis and light and electron microscopy. Blue and green light exposure markedly decreased expression of Rho and Opn4 mRNA and increased expression of Birc5 and c-Fos mRNA (P < 0.05). In retinas from the blue-light group, loss and vesiculation of photoreceptor outer segments were visible, but not in retinas from the red-light and control group. Measurements of the photoreceptor inner and outer segments length revealed, that this length was significantly decreased in the blue- and green-light exposure groups (P < 0.02), but not in the red-light exposure group. Increased expression of Birc5 and decreased expression of Rho and Opn4 after exposure to blue and green light may be early responses that help to reduce light-induced retinal damage.